2015
DOI: 10.1016/j.neuroimage.2015.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian segmentation of brainstem structures in MRI

Abstract: In this paper we present a method to segment four brainstem structures (midbrain, pons, medulla oblongata and superior cerebellar peduncle) from 3D brain MRI scans. The segmentation method relies on a probabilistic atlas of the brainstem and its neighboring brain structures. To build the atlas, we combined a dataset of 39 scans with already existing manual delineations of the whole brainstem and a dataset of 10 scans in which the brainstem structures were manually labeled with a protocol that was specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
186
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 38 publications
3
186
0
1
Order By: Relevance
“…The FreeSurfer 6.0 version, which allows for automatic calculation of medulla, pons, midbrain and superior cerebellar peduncle volumes, is based on a probabilistic atlas and a Bayesian segmentation (Iglesias et al, 2015). In order to avoid data irregularities stemming from the use of multiple workstations, all subjects were post-processed on a single Macintosh computer (osX: 10.10.5, Model: MacPro 6.1, Processor: 3.7 Quad-Core Intel Xeon E5, and RAM: 16GB 1866 MHz DDR3 ECC) in accordance with the manual guidelines used by FreeSurfer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FreeSurfer 6.0 version, which allows for automatic calculation of medulla, pons, midbrain and superior cerebellar peduncle volumes, is based on a probabilistic atlas and a Bayesian segmentation (Iglesias et al, 2015). In order to avoid data irregularities stemming from the use of multiple workstations, all subjects were post-processed on a single Macintosh computer (osX: 10.10.5, Model: MacPro 6.1, Processor: 3.7 Quad-Core Intel Xeon E5, and RAM: 16GB 1866 MHz DDR3 ECC) in accordance with the manual guidelines used by FreeSurfer.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, parcelletion of brainstem sub-structures could not be achieved using automated brain parcellation algorithms, leaving changes in the structural anatomy of individual brainstem structures in migraine relatively unexplored. The most recent structural pipeline of FreeSurfer 6.0 includes the capability to segment brainstem regions, and shows good performance relative to manual labeling techniques, which are time-consuming and operator-dependent (Iglesias et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The atlas consists in a data set of 49 manually labeled with a protocol that was specifically designed for the study and fully described in (Iglesias et al, 2015). This segmentation method relies on a probabilistic atlas of the brainstem and its neighboring brain structures.…”
Section: Automated Methods For Brainstem Segmentationmentioning
confidence: 99%
“…However, another multicenter study showed high sensitivity/specificity for the MRPI in differentiating PSP‐RS and PD and showed that an automated MRPI measurement that does not rely on rater reliability performs as well as a manual MRPI measurement . Automated methods for measuring midbrain volume are also now available and may improve standardization.…”
Section: Structural Mrimentioning
confidence: 99%